Gill Transcriptomic Responses to Toxin-producing Alga Prymnesium parvum in Rainbow Trout - Clinton, Morag; Król, Elżbieta; Sepúlveda, Dagoberto; Andersen, Nikolaj R.; Brierley, Andrew S.; Ferrier, David E. K.; Hansen, Per Juel; Lorenzen, Niels; Martin, Samuel A. M. (Frontiers in Immunology, 2021)
The gill of teleost fish is a multifunctional organ involved in many physiological processes, including protection of the mucosal gill surface against pathogens and other environmental antigens by the gill-associated lymphoid tissue (GIALT). Climate change associated phenomena, such as increasing frequency and magnitude of harmful algal blooms (HABs) put extra strain on gill function, contributing to enhanced fish mortality and fish kills. However, the molecular basis of the HAB-induced gill injury remains largely unknown due to the lack of high-throughput transcriptomic studies performed on teleost fish in laboratory conditions. We used juvenile rainbow trout (Oncorhynchus mykiss) to investigate the transcriptomic responses of the gill tissue to two (high and low) sublethal densities of the toxin-producing alga Prymnesium parvum, in relation to non-exposed control fish. The exposure time to P. parvum (4–5 h) was sufficient to identify three different phenotypic responses among the exposed fish, enabling us to focus on the common gill transcriptomic responses to P. parvum that were independent of dose and phenotype. The inspection of common differentially expressed genes (DEGs), canonical pathways, upstream regulators and downstream effects pointed towards P. parvum-induced inflammatory response and gill inflammation driven by alterations of Acute Phase Response Signalling, IL-6 Signalling, IL-10 Signalling, Role of PKR in Interferon Induction and Antiviral Response, IL-8 Signalling and IL-17 Signalling pathways. While we could not determine if the inferred gill inflammation was progressing or resolving, our study clearly suggests that P. parvum blooms may contribute to the serious gill disorders in fish. By providing insights into the gill transcriptomic responses to toxin-producing P. parvum in teleost fish, our research opens new avenues for investigating how to monitor and mitigate toxicity of HABs before they become lethal.